(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
subjected to atmospheric pressure changes and have an influence on flights. Barodontalgia is caused whenever the pulp is exposed to differential pressure gradient. Objective: To see the barodontalgia among aircrew of Bangladesh Air Force. Methodology: A cross-sectional study was carried out in Dental wing medical squadron BAF base Basher Dhaka. The study participants were recruited during one year among all the pilots and crewmembers attending departments specializing in medical follow-up at the study period from the Bangladesh Air Force. Results: Among the 50 barodontalgia group, most 39(78%) of the respondents were found technical and military flying whereas 50 without barodontalgia group 38(76%) specifically in military flying. In barodontalgia, 62% respondents were found in moderate pain (4-6), 26% in mild pain (1-3) and 32% in severe pain (7-10). In barodontalgia, 50% respondents were descent of barodontalgia, 52% were altitude where barodontalgia was reported to appear during the flight was <4000 meters and 70% were flight speed was 500-1000 km/h. Most of the respondents were found specifically in commercial flights in patients with barodontalgia. Majority pain intensity was found moderately in barodontalgia JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 186-188